2019
DOI: 10.1016/j.heliyon.2019.e01627
|View full text |Cite
|
Sign up to set email alerts
|

Current research aspects in mono and hybrid nanofluid based heat pipe technologies

Abstract: Technological development has leads to need of more compact thermal management system especially in electronic cooling systems. Heat pipe with the use of mono and hybrid nanofluids are recent trends to satisfy the need of enhanced heat transfer and miniaturization in size. In this article, a state-of-the-art review on different types of heat pipe s, nanofluids preparation and characterization techniques have been carried out. The study begins with an overview of heat pipe and discussed about heat pipe with sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 98 publications
0
32
0
Order By: Relevance
“…The hybrid nanofluids are new types of heat transfer nanofluids that have numerous applications in various fields such as electronic cooling, car radiators, heat pipes and heat exchanger, coolant in welding and machining, nuclear plants, and so on. Applications of heat pipe in the presence of mono-and multiple-nanoparticle mixtures with the base fluids were investigated by Bumataria et al 1 An experimental design approach for the thermal performance of hybrid nanofluid due to a double-pipe heat exchanger was examined by Maddah et al 2 A comprehensive review on the performance of hybrid nanofluids was provided by Hamzah et al 3 Huminic and Huminic 4,5 presented the behavior of hybrid nanofluids for heat transfer applications under laminar and turbulent flows at various temperatures and volume fractions. A study on the hybrid nanoparticle mixture, development, and applications is reported in References [6][7][8][9][10] The authors of these studies concluded that the hybrid nanofluids have superior thermophysical properties and heat transfer performance as compared with single nanofluid particles.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid nanofluids are new types of heat transfer nanofluids that have numerous applications in various fields such as electronic cooling, car radiators, heat pipes and heat exchanger, coolant in welding and machining, nuclear plants, and so on. Applications of heat pipe in the presence of mono-and multiple-nanoparticle mixtures with the base fluids were investigated by Bumataria et al 1 An experimental design approach for the thermal performance of hybrid nanofluid due to a double-pipe heat exchanger was examined by Maddah et al 2 A comprehensive review on the performance of hybrid nanofluids was provided by Hamzah et al 3 Huminic and Huminic 4,5 presented the behavior of hybrid nanofluids for heat transfer applications under laminar and turbulent flows at various temperatures and volume fractions. A study on the hybrid nanoparticle mixture, development, and applications is reported in References [6][7][8][9][10] The authors of these studies concluded that the hybrid nanofluids have superior thermophysical properties and heat transfer performance as compared with single nanofluid particles.…”
Section: Introductionmentioning
confidence: 99%
“…Their model was then employed by Saqib et al 41 for investigation of natural convection flow of a hybrid nanofluid between two infinite vertical parallel plates. In literature survey, other recent investigations on hybrid nanofluids have been conducted by [42][43][44][45][46][47][48][49][50][51][52][53] .…”
mentioning
confidence: 99%
“…However, there is a need for low‐cost nanoparticles to make a smooth transition from conventional coolants to nanofluids/coolants. Aluminum oxide (Al 2 O 3 ) nanoparticles are one of such low cost and promising candidate for high heat transfer rates 5‐7 …”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles concentration was varied from 1% to 5% for specific Reynolds numbers (1, 10, and 100) and reported a substantial improvement in heat transport with increasing concentration of nanoparticles 12 . Recently, Al 2 O 3 /Water nanofluids were also used for effective and rapid heat transfer during cutting process in manufacturing sector 7,13 …”
Section: Introductionmentioning
confidence: 99%